2019
DOI: 10.1101/784090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced Kv3.1 Activity in Dentate Gyrus Parvalbumin Cells Induces Vulnerability to Depression

Abstract: Parvalbumin (PV)-expressing interneurons are important for cognitive and emotional behaviors.These neurons express high level of p11, a protein associated with depression and action of antidepressants. Here we show that either specific deletion of p11 (p11 cKO) or chemogenetic inhibition in dentate gyrus (DG) PV neurons leads to anxiety-like behavior and susceptibility to depression in mice. DG PV neurons from p11 cKO mice showed reduced level and function of Kv3.1, and consequentially reduced capacity of high… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Taken together, these studies altogether suggest the PV inhibition as a common cellular mechanism associated with biological resilience as well as pharmacological actions of two different classes of antidepressants. Interestingly, a recent study by Medrihan et al suggested that decreased Kv3.1 channel and p11 function in PV vDG would confer susceptibility after stress (52). Although Ahnak cKO PV mice show resilience after CSDS (Figure 5F-J), p11 cKO PV mice show stress-susceptibility after SSDS(52), likely through many other binding partners of p11 in PV vDG including mGluR5, SMARCA3 and Supt6 (16,19).…”
Section: Discussionmentioning
confidence: 91%
“…Taken together, these studies altogether suggest the PV inhibition as a common cellular mechanism associated with biological resilience as well as pharmacological actions of two different classes of antidepressants. Interestingly, a recent study by Medrihan et al suggested that decreased Kv3.1 channel and p11 function in PV vDG would confer susceptibility after stress (52). Although Ahnak cKO PV mice show resilience after CSDS (Figure 5F-J), p11 cKO PV mice show stress-susceptibility after SSDS(52), likely through many other binding partners of p11 in PV vDG including mGluR5, SMARCA3 and Supt6 (16,19).…”
Section: Discussionmentioning
confidence: 91%
“…Such regulation includes different transcriptional programs controlling endocytosis [35]. In a recent study, we elucidated the involvement of p11, a SMARCA3-activity regulator protein, in modulating the endocytosis of potassium channel Kv3.1 in DG interneurons [36], suggesting that p11-SMARCA3 signaling mediates an endocytic program to regulate the activity of DG interneurons. Collectively, these findings support the idea that the p11-SMARCA3-Neurensin-2 signaling dynamically regulates a cellular endocytosis program in DG interneurons to mediate their function, AMPAR signaling, and consequently, to modulate emotional behavior.…”
Section: Neurensin-2 As a Potential Mediator Of Ampar Shuttling In Inmentioning
confidence: 98%
“…The behavioral response to chronic antidepressant treatment is mediated by p11 in DG cells, including cholecystokinin (CCK) [30] and parvalbumin (PV) [23] inhibitory interneurons, and the excitatory Mossy cells [31]. Among these, the two inhibitory interneurons also express Neurensin-2 , mirtazapine (mir), imipramine (imi), citalopram (cit) or fluoxetine (flx).…”
Section: P11-smarca3 Pathway In Parvalbumin-expressing Interneurons Mmentioning
confidence: 99%
“…We previously reported that chronic SSRIs and the subsequential induction in BDNF result in the upregulation of the antidepressant protein p11 [19,20]. p11 expression in the hippocampus is highly linked toresilience to stress and to the therapeutic effects of SSRIs [20][21][22][23]. Following chronic SSRIs, p11 binds SWI/ SNF-related, matrix-associated, actin-dependent regulator of chromatin 3 (SMARCA3) to mediate the behavioral response to the treatment [21,24].…”
Section: Introductionmentioning
confidence: 99%